Epibiotic Fauna on Cetaceans Worldwide: A Systematic Review of Records and Indicator Potential - S. Ten; J. A. Raga; F. J. Aznar (Frontiers in Marine Science, 2022)
Each individual cetacean is an ecosystem itself, potentially harboring a great variety of animals that travel with it. Despite being often despised or overlooked, many of these epizoites have been proven to be suitable bio-indicators of their cetacean hosts, informing on health status, social interactions, migration patterns, population structure or phylogeography. Moreover, epizoites are advantageous over internal parasites in that many of them can be detected by direct observation (e.g., boat surveys), thus no capture or dissection of cetaceans are necessary. Previous reviews of epizoites of cetaceans have focused on specific geographical areas, cetacean species or epibiotic taxa, but fall short to include the increasing number of records and scientific findings about these animals. Here we present an updated review of all records of associations between cetaceans and their epibiotic fauna (i.e., commensals, ecto- or mesoparasites, and mutualists). We gathered nearly 500 publications and found a total of 58 facultative or obligate epibiotic taxa from 11 orders of arthropods, vertebrates, cnidarians, and a nematode that are associated to the external surface of 66 cetacean species around the globe. We also provide information on the use as an indicator species in the literature, if any, and about other relevant traits, such as geographic range, host specificity, genetic data, and life-cycle. We encourage researchers, not only to provide quantitative data (i.e., prevalence, abundance) on the epizoites they find on cetaceans, but also to inform on their absence. The inferences drawn from epizoites can greatly benefit conservation plans of both cetaceans and their epizoites.